Structural Behavior of Thin-Walled Metal Silos Subject to Different Flow Channel Sizes under Eccentric Discharge Pressures - Sadowski, Adam J; Rotter, J. Michael (Journal of structural engineering (New York, N.Y.), 2012)
AbstractThe condition of eccentric discharge is known to be one of the most critical for the design of thin-walled cylindrical metal silos. Significant progress has been made in recent years in devising a relatively realistic set of representative pressures for this load case. However, the consequences these may have on the predicted structural behavior of a silo are not yet fully understood. This paper presents a detailed parametric study into the behavior of a custom-designed slender silo under a set of unsymmetrical pressures describing the action of an eccentric parallel-sided pipe flow channel of varying cross-sectional areas. The results are compared with the reference axisymmetric case of concentric discharge. It is found that the predicted behavior is very complex indeed, and that geometric nonlinearity is of much greater significance for cylindrical shells under unsymmetrical load patterns than under symmetrical patterns. Further, it is found that eigenmode-affine imperfections, which are very deleterious under axisymmetric loading patterns, are instead beneficial to the buckling strength of a silo under eccentric discharge, thus making them unsuitable for use in design for this load condition.